2004
DOI: 10.1080/0140672042000277107
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, inclusion and widening participation: a model of interactive teaching and leadership

Abstract: Interactive whole-class teaching is championed by the English National Curriculum and the accompanying National Literacy and National Numeracy Strategies. Inspection of the related literature, however, reveals no corresponding pedagogy, which is also lacking in earlier 'interactive' initiatives. The paper considers how traditional 'hierarchical' perceptions have undermined the 'practical' prescriptions given and neglected attitudinal influences. It argues that this practical deficit, aspects of teacher educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It was found that engaging them early on has a significant impact on implementation. School leaders in the Jones’ (2004) study not only engaged parent stakeholders but widened their participation by finding ways to collaborate with mothers, and not only fathers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that engaging them early on has a significant impact on implementation. School leaders in the Jones’ (2004) study not only engaged parent stakeholders but widened their participation by finding ways to collaborate with mothers, and not only fathers.…”
Section: Resultsmentioning
confidence: 99%
“…Much of the literature described how institutional leaders interact with the people in their institutions. They start by creating structures that support the functioning of the institution (Bürgin, 2018; Jones, 2004). Successful leaders create a balance that facilitates communication across the institution (Elezi & Bamber, 2018), ensure that constituent units do not operate as ‘silos’ (Mitchell, 2018) and do not allow one unit to have unbalanced power over the institution (Gurd & Helliar, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations